Advances in Navigability and Mooring (MDPI - Multidisciplinary Digital Publishing Institute, 2025)
Focusing on navigation, port design, and security, this collection of research papers comprehensively examines the latest advances and challenges in the maritime industry. As the maritime sector evolves with the introduction of larger vessels and advanced technologies, this book addresses critical topics such as navigational safety, efficient port logistics, and the integration of cybersecurity measures. Topics covered include real-time simulation methods for ship maneuvers, the impact of environmental factors on navigation, and the role of human factors in maritime decision-making. By summarizing the results of various studies, this book provides valuable insights for marine engineers, naval architects, maritime safety professionals, and researchers. Intended for both academic discourse and practical application, this collection is an important resource for anyone working in the maritime field. Whether you are a seasoned professional or a newcomer to the industry, the research presented here will deepen your understanding of the complexities and opportunities of maritime operations, while keeping the reader informed of current developments and requirements, the most challenging development being the increasing role of the industry in adjusting to the ever expanding sizes of vessels, which adds to the challenge of maintaining safety in virtually all topics of research into the industry.